2021
DOI: 10.1371/journal.pone.0254988
|View full text |Cite
|
Sign up to set email alerts
|

Trends of global health literacy research (1995–2020): Analysis of mapping knowledge domains based on citation data mining

Abstract: Background During uncertainties associated with the COVID-19 pandemic, effectively improving people’s health literacy is more important than ever. Drawing knowledge maps of health literacy research through data mining and visualized measurement technology helps systematically present the research status and development trends in global academic circles. Methods This paper uses CiteSpace to carry out a metric analysis of 9,492 health literacy papers included in Web of Science through mapping knowledge domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Schillinger published 17 articles (0.9%), ranking third for publications. Accordingly, we found that some of the most productive authors, namely, Wolf and Schillinger [ 25 ], were also the most productive in the field of health literacy. In addition, we investigated the h-index and found that Stellefson’s research may have had great impaction in the fields of digital health literacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schillinger published 17 articles (0.9%), ranking third for publications. Accordingly, we found that some of the most productive authors, namely, Wolf and Schillinger [ 25 ], were also the most productive in the field of health literacy. In addition, we investigated the h-index and found that Stellefson’s research may have had great impaction in the fields of digital health literacy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is some bibliometric research related to health literacy and eHealth literacy [ 25 - 27 ]. However, although these studies have done systematic bibliometrics, their core concepts are limited to eHealth literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions targeting general health literacy were also less numerous than interventions targeting mental health literacy [ 75 ]. In recent years, mental health literacy was the area of most research activities in health literacy research [ 21 ]. Mental health literacy refers to the knowledge and beliefs about mental disorders that support their detection, management, or prevention [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of health literacy, and especially of health literacy addressing knowledge and skills in occupational settings, can lead to improved individual skills, less occupational hazards and injuries, and to the maintenance and promotion of work ability. In the past five years, interdisciplinary collaborations in health literacy research evolved between, for example, environmental or occupational health, public health, and nursing [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 Bibliometrics played a unique role in quantifying knowledge production and laws of scientific development. 34 Bibliometric Analysis of food big data, 35 food waste, 36 global climate change, 37 food safety governance, 38 global health literacy, 39 eHealth 40 , 41 and eHealth literacy 42 were reported. However, the bibliometric studies on eHealth are mainly about competencies or knowledge structures.…”
Section: Introductionmentioning
confidence: 99%